Modeling of Sustainability Knowledge: Under Perception on Entrepreneurship Students - Kartika Nuringsih; Edalmen Edalmen; Nuryasman M. N. (Graduate Program of Universitas Tarumanagara, 2023)
As aligning with sustainability issues, the study generates about modeling of sustainability knowledge with a factor analysis approach based on sustainable development goals (SDGs). The population involves entrepreneurial students with processing techniques using factor analysis using SPSS (n=150). The result of testing the Principal Component Analysis method provides the largest contribution of 57.817% with forming four components grouped in Component 1. However, the result is not logical so a rotation process is carried out with several methods including Equamax. After rotating, it produces four components, namely: Component 1 includes SDGs_3, SDGs_4, SDGs_7, SDGs_13, SDGs_17 with the name domain of social equity. Component 2 includes SDGs_9, SDGs_10, SDGs_11, SDGs_14, SDGs_15, SDGs_16 with domain of environmental sustainability. Component 3 includes SDGs_5, SDGs_6, SDGs_12 with the name domain of cultural responsibility. Lastly, Component 4 includes SDGs_1, SDGs_2, SDGs_8 with the domain of economic viability. Based on these results is concluded that the sustainable knowledge construct consists of four dimensions, such as social equity, environmental sustainability, cultural responsibility, and economic viability which are aligned with the pillars of sustainable development. It may be considered to enhance sustainability entrepreneurial learning at the university level.